LEGAL CERTAINTY OF MARRIAGE BETWEEN CHRISTIANS AND CATHOLICS IN THE DECISION OF THE NORTH JAKARTA DISTRICT COURT NUMBER 423/PDT.P/2023/PN JKT.UTR - Samuel Fajar Hotmangara Tua Siahaan; Rachmi Sulistyarini; Djumikasih (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Interfaith marriages can be registered by the state as long as there is a court decree declaring the validity of the marriage and registerable, as regulated in the act of marriage and act of population administration. This also applies to interchurch marriages between Catholics and Christians in Indonesia. Regarding this matter, The North Jakarta District Court issued Decree Number 423/Pdt.P/2023/PN Jkt.Utr, which granted the petitioners' request for registration of their interchurch marriages. However, in its legal reasoning, the Judge stated that the petitioners' interchurch marriage was not considered an interfaith marriage. Furthermore, the Judge did not obtain evidence of the Christian Church's approval of their interchurch marriage. Through this study of this decree, the author conducted legal research using a statutory, a conceptual, and a systematic approach, thus concluding that the decree order does not fulfill the principle of legal certainty.